The Use of Skin Staples as Fiducial Markers to Confirm Intraoperative Spinal Navigation Registration and Accuracy. Issue 3 (26th May 2021) - Alvarez-Breckenridge, Christopher; Muir, Matthew; Rhines, Laurence D; Tatsui, Claudio E
Abstract: BACKGROUND: With the advent of intraoperative computed tomography (CT) for image guidance, numerous examples of accurate navigation being applied to cranial and spinal pathology have come to light. For spinal disorders, the utilization of image guidance for the placement of percutaneous spinal instrumentation, complex osteotomies, and minimally invasive approaches are frequently utilized in trauma, degenerative, and oncological pathologies. The use of intraoperative CT for navigation, however, requires a low target registration error that must be verified throughout the procedure to confirm the accuracy of image guidance. OBJECTIVE: To present the use of skin staples as a sterile, economical fiducial marker for minimally invasive spinal procedures requiring intraoperative CT navigation. METHODS: Staples are applied to the skin prior to obtaining the registration CT scan and maintained throughout the remainder of the surgery to facilitate confirmation of image guidance accuracy. RESULTS: This low-cost, simple, sterile approach provides surface landmarks that allow reliable verification of navigation accuracy during percutaneous spinal procedures using intraoperative CT scan image guidance. CONCLUSION: The utilization of staples as a fiducial marker represents an economical and easily adaptable technique for ensuring accuracy of image guidance with intraoperative CT navigation.